The role of small-scale fisheries in Nigeria’s food system - Byrd, Kendra; Fakoya, Kafayat; Akintola, Shehu; Westlund, Lena; Isa, Suleiman; Cohen, Philippa (WorldFish, 2022)
This discussion paper draws together recent data on fish and aquatic foods, and nutrition in Nigeria, to examine how small-scale fisheries fit within and contribute to Nigeria’s food system. Much of the analysis and exploration we present here are of very recent data from global, national, and local initiatives. This discussion paper has a particular focus on Sustainable Development Goals 2, and other goals and targets related to human nutrition, food security, and sustainable food production and supplies.